From present to future, from a relative security to a worrying insecurity - Lupu, Mădălina-Elena (Technium Social Sciences Journal, 2025)
In our previous research, we focused on the Ukraine Invasion as a reference point, on the Russian state effects after the invasion and on the new security architecture in the 21st century that was determined by the Russian Federation actions in Ukraine. In this article, we extend the research and look into the future by approaching the security concept from a transitory perspective, from relative security to worrying insecurity. It begins with a brief look at 20th century insecurity. It continues with threats and challenges to security and with the measures that have been taken recently by the Russian proximity border states in order to strengthen their security after the Ukraine Invasion. It ends with highlighting the Great Powers that project these threats and challenges, the Russian Federation and China.